2021
DOI: 10.1016/j.jshs.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interrupting prolonged sitting on postprandial glycemia and insulin responses: A network meta-analysis

Abstract: Highlights Interrupting prolonged sitting with physical activity breaks is effective in controlling postprandial glycemia and insulin responses. Intermittently interrupting sitting with moderate-intensity physical activity is the optimal intervention strategy in reducing postprandial glycemia and insulin responses. At least a 2-min activity break every 20–30 min to interrupt prolonged sitting reduces postprandial glycemia and insulin responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
(123 reference statements)
2
7
0
Order By: Relevance
“…Nonetheless, our findings suggest that sedentary breaks every 60 min may not be an efficacious frequency for the lowering of glucose at a given sedentary break duration of 1 or 5 min; albeit further research is needed to determine if a higher sedentary break duration (i.e., 10 min) or intensity (i.e., moderate or vigorous) would yield stronger effects at this frequency. Our findings are consistent with a recent network meta-analysis, which identified a sedentary break frequency of every 20 to 30 min as the optimal frequency for reducing postprandial glycemic responses (35). We extend upon this work and confirm the efficacy of the every 30 min sedentary break frequency within the context of a single study, which permits direct comparisons of dose under identical controlled laboratory settings.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, our findings suggest that sedentary breaks every 60 min may not be an efficacious frequency for the lowering of glucose at a given sedentary break duration of 1 or 5 min; albeit further research is needed to determine if a higher sedentary break duration (i.e., 10 min) or intensity (i.e., moderate or vigorous) would yield stronger effects at this frequency. Our findings are consistent with a recent network meta-analysis, which identified a sedentary break frequency of every 20 to 30 min as the optimal frequency for reducing postprandial glycemic responses (35). We extend upon this work and confirm the efficacy of the every 30 min sedentary break frequency within the context of a single study, which permits direct comparisons of dose under identical controlled laboratory settings.…”
Section: Discussionsupporting
confidence: 92%
“…Recent meta‐analyses have attempted to assess the effectiveness of interrupting prolonged sitting to lower postprandial glucose and insulin responses (26‐28). The effectiveness of physical activity breaks to lower postprandial glucose iAUC in people with obesity, impaired fasting glucose, or type 2 diabetes greatly varied across 24 studies presented within a meta‐analysis by Loh et al (26).…”
Section: Discussionmentioning
confidence: 99%
“…Even a simple standing interrupting behavior could induce beneficial metabolic changes, such as making insulin, total cholesterol content and fast blood sugar in an inevitable decline ( 36 ). Besides, findings were also observed that ST Breaks times could significantly improve the body's glucose metabolism with no increase in total energy intake among overweight and obese children ( 37 ), and positively reduce postprandial hypoglycemia and insulin responses among adults ( 38 ). The result seems to provide an effective way to improve the overweight state of children and adolescents.…”
Section: Discussionmentioning
confidence: 98%